2010
DOI: 10.1111/j.1365-2567.2009.03174.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of the NALP3 inflammasome in rheumatoid synovium

Abstract: Summary The NACHT, LRR and PYD domains containing protein (NALP3) inflammasome is a key regulator of interleukin‐1β (IL‐1β) secretion. As there is strong evidence for a pro‐inflammatory role of IL‐1β in rheumatoid arthritis (RA) and in murine models of arthritis, we explored the expression of the different components of the NALP3 inflammasome as well as other nucleotide oligomerization domain (NOD)‐like receptors (NLRs) in synovium obtained from patients with RA. The expression of NLRs was also studied in fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 17 publications
4
66
3
2
Order By: Relevance
“…ASC has been identified as the regulator of NF-B and MAPK/ERK-2 activity in murine and human monocytes/ macrophages (42,43). The disease progression in the mouse model of autoimmune arthritis is attenuated in mice lacking ASC, but not in caspase 1 Ϫ/Ϫ mice (44,45). Further, Ichinohe et al reported that nasal IgA and systemic IgG responses against influenza virus required ASC, but not NLRP3 (26).…”
Section: Discussionmentioning
confidence: 99%
“…ASC has been identified as the regulator of NF-B and MAPK/ERK-2 activity in murine and human monocytes/ macrophages (42,43). The disease progression in the mouse model of autoimmune arthritis is attenuated in mice lacking ASC, but not in caspase 1 Ϫ/Ϫ mice (44,45). Further, Ichinohe et al reported that nasal IgA and systemic IgG responses against influenza virus required ASC, but not NLRP3 (26).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the inflammasome components in OA synovium has been described and active caspase-1 has been detected with markedly increased cellularity in articular cartilage of human OA (36)(37)(38). Here we demonstrated that in comparison with the human monocytic cell line THP1, the expressions of ASC, caspase-1, and especially NLRP3 mRNA were very low in CD33 − nonhematopoietic cells, including primary human chondrocytes and synoviocytes derived from OA patients (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…The NLRP3 inflammasome is also activated in RA synovium, consistent with increased IL-1β secretion (110,111). TNF-α stimulates IL-1β expression in vitro, suggesting the latter cytokine may drive pro-IL-1β transcription in RA.…”
Section: Skeletal Changes Associated With Excessive Inflammasome Actimentioning
confidence: 67%